2022
DOI: 10.1021/acs.jproteome.1c00879
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Human Milk Dynamics: Interindividual Variation in Milk Proteome, Peptidome, and Metabolome

Abstract: Human milk is a dynamic biofluid, and its detailed composition receives increasing attention. While most studies focus on changes over time or differences between maternal characteristics, interindividual variation receives little attention. Nevertheless, a comprehensive insight into this can help interpret human milk studies and help human milk banks provide targeted milk for recipients. This study aimed to map interindividual variation in the human milk proteome, peptidome, and metabolome and to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
(141 reference statements)
1
9
0
Order By: Relevance
“…The protein concentration was determined with the Pierce bicinchonic acid (BCA) assay (Thermo Scientific, Waltham, MA), and samples were diluted in 100 mM Tris to a concentration of 1 µ g/ µ L protein. The diluted skimmed milk samples were prepared with filter-aided sample preparation (FASP) for protein analysis in randomized order as previously described ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was determined with the Pierce bicinchonic acid (BCA) assay (Thermo Scientific, Waltham, MA), and samples were diluted in 100 mM Tris to a concentration of 1 µ g/ µ L protein. The diluted skimmed milk samples were prepared with filter-aided sample preparation (FASP) for protein analysis in randomized order as previously described ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned previously, all proteins exhibit higher inter-individual variabilities than the variation of the same individual on different days. This trend has also been reported in other biofluids. Lipocalin-1 and lysozyme C are two of the most abundant proteins in tears, and both exhibited relatively low inter-day and inter-individual variabilities from this analysis. Serum albumin is also a highly abundant protein but interestingly showed a much higher variation.…”
Section: Resultsmentioning
confidence: 99%
“…In our studies, we observed a reduction in AOPP in colostrum when the dietary variables of lactating women were not considered. The artificial substances in soft drinks, constituting a significant portion of their composition, promote the generation of free radicals, which have known adverse effects extensively studied, including their association with cardiovascular diseases, Type 2 diabetes, and autism, among other conditions (Dekker et al, 2022; Lu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Their degradation can lead to changes in their function, thereby altering the formation of the intestinal microbiome. The consequences of the degradation of these nutrients can be unpredictable (Dekker et al, 2022; Dingess et al, 2021; Lawrence, 2022).…”
Section: Introductionmentioning
confidence: 99%